Économie circulaire, mines urbaines et altermétropolisation : une expérience française - Maxime Schirrer (Bulletin de l’Association de Géographes Français)
Urban landfill refers to all e-waste that is not used for reuse, repair, re-employment. In the aftermath of the Covid 19 global pandemic, disruptions to the supply chain and the supply of raw materials have had an impact on the growth model based on the digital economy. Urban mines are therefore at the heart of industrial strategies, and their recognition as an issue of national sovereignty raises the question of whether they can form the basis of a large-scale circular economy.